2017
DOI: 10.1021/acs.analchem.7b04335
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Alpha-Synuclein Protein Analysis from Human Brain Tissues Using Single-Molecule Pull-Down Assay

Abstract: Alpha-synuclein (α-SYN) is a central molecule in Parkinson's disease pathogenesis. Despite several studies, the molecular nature of endogenous α-SYN especially in human brain samples is still not well understood due to the lack of reliable methods and the limited amount of biospecimens. Here, we introduce α-SYN single-molecule pull-down (α-SYN SiMPull) assay combined with in vivo protein crosslinking to count individual α-SYN protein and assess its native oligomerization states from biological samples includin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 38 publications
0
24
1
Order By: Relevance
“…While many previous studies characterizing α-synuclein aggregates by size have been conducted in vitro, more research remains to be done on identifying the soluble aggregates present in the human brain. Endogenous levels of α-synuclein aggregates were measured in the substantia nigra in control and PD post-mortem tissue by Je et al at the single-molecule level 42 . They reported that the oligomeric species accounted for 56% of the α-synuclein species in the PD samples but only 23% in non-PD control samples.…”
Section: Introductionmentioning
confidence: 99%
“…While many previous studies characterizing α-synuclein aggregates by size have been conducted in vitro, more research remains to be done on identifying the soluble aggregates present in the human brain. Endogenous levels of α-synuclein aggregates were measured in the substantia nigra in control and PD post-mortem tissue by Je et al at the single-molecule level 42 . They reported that the oligomeric species accounted for 56% of the α-synuclein species in the PD samples but only 23% in non-PD control samples.…”
Section: Introductionmentioning
confidence: 99%
“…(e) oligomers and fibrils of amyloid aggregates super resolved using DNA-PAINT (reproduced with permission from ( Whiten et al, 2018a )). (f) SiMPull of αS aggregates in postmortem brain punches from patients with and without PD (reproduced with permission from ( Je et al, 2017 )). …”
Section: Single Molecule Microscopy Of Protein Aggregatesmentioning
confidence: 99%
“…We have previously discussed SiMPull as a simple, yet powerful, tool for measuring the composition of protein complexes with single molecule precision. In a recent study, αS SiMPull was applied to post mortem brains of humans diagnosed with PD as well as healthy controls to image endogenous αS aggregates ( Je et al, 2017 ). To make these measurements, aggregates were sandwiched between 2 antibody systems: a primary and secondary capture antibodies which hook the aggregates to a Polyethylene glycol (PEG) coated coverslip and, another, primary and secondary detection antibodies of which the latter is conjugated to a synthetic fluorophore as a reporter.…”
Section: Biological Insights From the Application Of Single Molecule Microscopy To Protein Aggregatesmentioning
confidence: 99%
“…SiMPull can offer a potential means to clarify the behavior of these proteins while ensemble methods such as SDS‐PAGE or gel‐filtration can yield controversial results (Burré et al, ). By analyzing the intensity of captured single‐molecule spots, SiMPull performed on lysate solutions from human brain tissue showed higher levels of both overall α‐SYN and oligomeric α‐SYN in PD patients (Je et al, ). This method is applicable to diverse biospecimens including cerebrospinal fluid, blood and tear fluid.…”
Section: Protein Analysis Using Pull‐down Assaysmentioning
confidence: 99%
“…Recently, SiMPull has further extended its application areas to neurodegenerative diseases (Je et al, 2017). Parkinson's disease (PD) and Alzheimer's disease are notoriously difficult to diagnose without a postmortem brain biopsy, and the proteins involved in their pathogenesis have been challenging to study.…”
Section: Protein Analysis Using Pull-down Assaysmentioning
confidence: 99%